Cover Feature: Altered Lipid Composition of Secretory Cells Following Exposure to Zinc Can Be Correlated to Changes in Exocytosis (Chem. Eur. J. 21/2019). Issue 21 (18th March 2019) - Ren, Lin; Dowlatshahi Pour, Masoumeh; Malmberg, Per; Ewing, Andrew G.
Abstract : By combining electrochemical techniques and mass spectrometry imaging, zinc has been shown to significantly change the dynamics of exocytosis and the vesicle contents, as well as the lipid distribution on the cell membrane. Altered lipid composition after zinc exposure can be correlated to changes in exocytosis, which provides direct evidence that zinc regulates neurotransmitter release and results in the modulation of synaptic strength and plasticity. More information can be found in the Communication by A. G. Ewing et al. on page 5406 .